Senecio espiritosantensis (Compositae: Senecioneae), a new species from Espírito Santo, Brazil - Teles, Aristônio Magalhães (Phytotaxa, 2018)
During a taxonomic study of the tribe Senecioneae (Compositae) of Brazil, a new species, Senecio espiritosantensis, was discovered and is described, discussed and illustrated here. This new species is closely related to S. hatschbachii and S. macrotis. Senecio espiritosantensis belongs to S. sect. Cacaliastrum due to its growth habit, large petiolate leaves, radiate capitula and paniculiform capitulescence. A key to the species of S. sect. Cacaliastrum is provided.